EPIDEMIOLOGY AND RISK FACTORS OF BREAST CANCER: A GLOBAL PERSPECTIVE ON INCIDENCE, MORTALITY, AND PREVENTION STRATEGIES - KHALID, S; ARSHAD, S; AQEEL, M; AMEER, R; SHAUKAT, A; GHOUS, M; KHALIQ, H; DAR, SA; SHAHID , A (Biological and Clinical Sciences Research Journal, 2024)
Breast cancer is the most prevalent malignancy among women worldwide, contributing significantly to global cancer mortality. This review provides a detailed examination of the epidemiological trends, molecular subtypes, and risk factors associated with breast cancer, with a focus on disparities in incidence, mortality, and survival across populations. Incidence rates are highest in developed regions, attributed to lifestyle and environmental factors, while mortality rates are disproportionately higher in developing countries due to limited healthcare access and aggressive tumor biology. The analysis highlights the pivotal role of genetic predispositions, such as BRCA mutations, alongside modifiable risk factors, including physical inactivity, obesity, alcohol consumption, and radiation exposure. Hormonal influences, reproductive behaviors, and dietary patterns further modulate individual risk profiles. Emerging evidence underscores the impact of socioeconomic disparities and ethnicity on breast cancer outcomes, particularly among African American and Hispanic women, who often present with more aggressive triple-negative subtypes and worse prognoses. Advancements in early detection, such as widespread mammography, have improved survival rates in developed countries, though challenges persist in low-resource settings. The review emphasizes the significance of understanding molecular subtypes—Luminal A, Luminal B, HER2-enriched, and triple-negative breast cancer—and their implications for targeted therapies. Innovations in genetic screening, personalized medicine, and lifestyle interventions are poised to transform prevention and treatment strategies globally. This review underscores the necessity of addressing healthcare inequities, promoting lifestyle modifications, and advancing molecular research to reduce the global burden of breast cancer. Future efforts should focus on integrating public health initiatives, enhancing access to diagnostic tools, and developing cost-effective therapies tailored to diverse populations. Bridging the gap between resource-rich and resource-limited regions is imperative for achieving equity in breast cancer care and outcomes.